Europe as a Stronger Global Actor - Duke, Simon. author. aut Link
XIII, 286 p. 1 illus.
Keywords: ‘This book provides an incisive account of the dilemmas faced by EU foreign policy whilst at the same time taking a specific and provocative point of view on the credentials of ‘European foreign policy’. There is no better-qualified person than Simon Duke to undertake this task, and the book will be much used by both policy-makers and students in the field.’ – Michael Smith, Professor of European Politics, University of Warwick, UK ‘This timely book provides a comprehensive analysis of the strategic challenges the European Union must confront if it is to become a more effective international and regional actor in the post-Cold War world. This extremely rich study includes original insight into the evolution of European Union foreign policy as it seeks to navigate the changing nature of Euro-Atlantic and Euro-Asia relations and manage the aftermath of the Arab Spring moment across the Mediterranean area. An essential read for policy makers, academics, students and anyone interested in achieving a better understanding of the prospects for a more dynamic European Union in contemporary global affairs.’ – Stephen Calleya, Professor Mediterranean Academy of Diplomatic Studies and Director, Mediterranean Academy of Diplomatic Studies, University of Malta ‘As the world enters a period of power transition, Europe faces greater challenges than at any time since 1945. In this original and lucid assessment of the cards the old continent holds, Simon Duke calls for radical new thinking to face up to a range of internal and external threats that, cumulatively, amount to an existential crisis. The approaches of the past fifty years, from strategic unconsciousness to normative hubris, must be discarded in favor of a far more realistic understanding of the emerging new world order. This book is a much needed wake-up call.’ – Jolyon Howorth, Visiting Professor of Political Science andInternational Affairs, Yale University, USA This book considers the principal challenges facing the European Union, which has been buffeted by a series of profound crises, both internal and external. The EU lacks a meta-narrative that could indicate priorities and linkages between the various responses to the global challenges it faces. As a result, the EU often appears to be a confusing and even contradictory actor to many international partners. It will continue to be so unless the EU develops a deeper sense of strategic awareness and confidence so that it may give a more convincing response to fundamental questions about the Union’s role, purpose and identity in a changing world. Simon Duke is Professor of European Policies at the European Institute of Public Administration. He is also a Senior Research Fellow at Maastricht University, the Netherlands. He is Executive Editor of the Journal of European Integration. < .